Is renal scintigraphy necessary after heminephrectomy in children?. Issue 1 (February 2016) - Strine, A.C.; Whittam, B.M.; Misseri, R.; Kaefer, M.; Rink, R.C.; Karmazyn, B.; Cain, M.P.
Summary: Introduction: Heminephrectomy remains an excellent option for a poorly functioning moiety in a duplicated collecting system. A primary concern during heminephrectomy is the potential for a significant functional loss in the remaining ipsilateral moiety. As the gold standard for the assessment of differential renal function, renal scintigraphy is often used in the postoperative evaluation of children undergoing heminephrectomy. However, this imaging modality is costly, invasive, and associated with exposure to radiation. Doppler renal ultrasound (RUS) avoids these concerns and is able to evaluate for structural and functional abnormalities. Objective: The present study sought to compare Doppler RUS to renal scintigraphy in determining the viability of the remaining ipsilateral moiety in children who underwent heminephrectomy for a poorly functioning moiety in a duplicated collecting system. Materials and Methods: The institutional database of children who underwent open heminephrectomy for a poorly functioning moiety in a duplicated collecting system between 2006 and 2013 was reviewed. Only children who underwent both a postoperative Doppler RUS and renal scan were included. A blinded pediatric radiologist independently reviewed all Doppler RUS. Vascular flow on Doppler RUS was correlated with the preservation of renal function in the remaining ipsilateral moiety on renal scintigraphy. Results: A total of 29 children were identified for inclusion. Demographic and operative data are provided in Table. The average pre-operative and postoperative differential renal function in the ipsilateral kidney was 41.6% and 38% on renal scintigraphy, respectively, for an average decrease of 3.6% (−18% to +12%). Doppler RUS demonstrated the presence of vascular flow to the remaining ipsilateral moieties of all children after heminephrectomy. Renal scintigraphy confirmed the viability of these moieties in all children. Discussion: The first study comparing Doppler RUS to renal scintigraphy was performed to determine the viability of the remaining ipsilateral moiety after heminephrectomy. While no cases of complete functional loss were observed, an average decrease of 3.6% in the ipsilateral renal function favorably compared with other series of children undergoing open heminephrectomy. The limitations of the study included its retrospective design at a single institution. The interpretation of Doppler RUS by an individual pediatric radiologist may also have lead to interobserver variability and impacted the reproducibility of the study, while the absence of any cases of complete functional loss may have impacted its generalizability. Conclusions: Doppler RUS is an accurate imaging modality for determining the viability of the remaining ipsilateral moiety after heminephrectomy and may obviate the need for renal scintigraphy.